(untitled) (Global Journal of Science Frontier Research, 2013)
Nairobi City the Capital of Kenya lies on the eastern flank of the Kenya Rift Valley. The geological succession includes metamorphic and igneous rocks as well as interbedded lacustrine and alluvial sediments. Groundwater has been encountered in aquifers within the thirteen different geologic units in the succession. The objective of this study was to analyse the geochemistry of groundwater for major and minor elements, heavy metals as well as the presence of pollutants. The 30 samples were collected and analysed using international standards. Membrane Filter Technique, Ion chromatography, Atomic Absorption Spectrometry and Inductively Coupled Plasma were some of the methods of analysis used. The results show that the physical parameters of the groundwater across the study area range from those within the recommended World Health Organisation limits to those that raise concern such as the high turbidity, pH and electrical conductivity values in boreholes in Embakasi, Industrial area, and Karen. Since these parameters signify potential for microbial contamination, a research should be carried out to analyse their variation and the relationship with lithology and structural geology of the area. Results of this study as well as those of past chemical analyses indicate that major anions and cations concentrations are within the limits recommended by WHO. High nitrate concentrations are detected in the shallow wells. Fluoride content is above internationally recommended limits in majority of the boreholes.